2013
DOI: 10.1002/cctc.201300416
|View full text |Cite
|
Sign up to set email alerts
|

Gold Catalysis Opens Up a New Route for the Synthesis of Benzimidazoylquinoxaline Derivatives from Biomass‐Derived Products (Glycerol)

Abstract: The reaction of unsubstitued camphanyl‐piperazine 4 with ZnCl2, phenylacetylene, and benzaldehyde in toluene gave the corresponding dipropargylamine (i.e., 15) with opposite configurations at the newly formed stereogenic centres, which, upon reaction with ZnI2 resulted in the formation of a racemic mixture of 1,3‐diphenyl allene in 45 % yield. N‐Methylcamphanyl‐piperazine regioisomer 5, prepared by selective N‐methylation of the NH moiety attached to the stereogenic centre with (S)‐configuration, upon reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
0
25
0
1
Order By: Relevance
“…Climent et al showed that glyceraldehyde 83 (or glycerol) undergoes oxidation-cyclization twice with o-phenylenediamine derivatives 109 to give various substituted benzimidazoylquinoxalines 115 (24-80% yields) catalyzed by ceria supported gold nanoparticles (Au/CeO 2 ) using air as the oxidant at 140°C for 24 h (Scheme 31). 254 In the reaction pathway, glyceraldehyde 83 ( possibly in situ generated from glycerol by oxidation) first proceeds coupling and cyclization with o-phenylenediamine derivatives 109 to produce the intermediate benzimidazol 114, followed by cascade oxidation-cyclization with another o-phenylenediamine 109 to afford the substituted benzimidazoylquinoxalines 115. The electron-donating substituents in the phenyl ring favor the competitive oxidative cleavage of the diol 114, and lead to a decrease in the product selectivity by formation of other azaheterocycles 116-119 (Scheme 31).…”
Section: Benzimidazolesmentioning
confidence: 99%
“…Climent et al showed that glyceraldehyde 83 (or glycerol) undergoes oxidation-cyclization twice with o-phenylenediamine derivatives 109 to give various substituted benzimidazoylquinoxalines 115 (24-80% yields) catalyzed by ceria supported gold nanoparticles (Au/CeO 2 ) using air as the oxidant at 140°C for 24 h (Scheme 31). 254 In the reaction pathway, glyceraldehyde 83 ( possibly in situ generated from glycerol by oxidation) first proceeds coupling and cyclization with o-phenylenediamine derivatives 109 to produce the intermediate benzimidazol 114, followed by cascade oxidation-cyclization with another o-phenylenediamine 109 to afford the substituted benzimidazoylquinoxalines 115. The electron-donating substituents in the phenyl ring favor the competitive oxidative cleavage of the diol 114, and lead to a decrease in the product selectivity by formation of other azaheterocycles 116-119 (Scheme 31).…”
Section: Benzimidazolesmentioning
confidence: 99%
“…A gold catalyst (Au/CeO 2 ) was used to synthesize benzimidazolylquinoxalines by two novel methods in a multistep one-pot methodology. 80 The rst method involved the oxidative coupling of glycerol 60 with 1,2-DAB 5a performed at C using diglyme as a solvent and lead to the benzimidazolylquinoxaline compound 63a through the formation of intermediates 61a and 62a (Scheme 18). Herein, the benzimidazolylquinoxaline possesses the same substituents in both heterocycles.…”
Section: From Glycerol and 12-diaminobenzenes With Use Of Gold Catalmentioning
confidence: 99%
“…hydroxymethylquinoxaline 61a, 1-(1H-benzo[d] imidazol-2-yl)ethane-1,2-diol 62a, and its protected derivative 80 were investigated (Scheme 21). 80 Following the optimization of the reaction conditions with different substrates, the results presented in Scheme 22 showed that only the reaction between glyceraldehyde and 1,2-DAB (Scheme 21, route c) in the presence of Au/CeO 2 , oxygen pressure, and at room temperature, produced the benzimidazole intermediate 62 with a high selectivity with complete conversion. Consequently, the synthesis of the benzimidazole intermediate from glyceraldehyde and 1,2-DAB derivative was chosen as the optimum rst step of the reaction.…”
Section: From Glycerol and 12-diaminobenzenes With Use Of Gold Catalmentioning
confidence: 99%
See 1 more Smart Citation
“…158 The scope of the reaction is shown in Table 12 by using a variety of different substituted amines and alcohols/aldehydes. The CeO 2 -supported gold nanoparticles prepared via deposition-precipitation method gave the moderate to good yields of benzimidazoylquinoxalines.…”
Section: Introductionmentioning
confidence: 99%